Thinking about critical thinking: An industry perspective. Issue 2 (April 2019) - Pearl, Alastair Owen; Rayner, Gerry M.; Larson, Ian; Orlando, Laurence
There has been a drive towards enhancing the critical thinking (CT) skills development of students in the science, technology, engineering and mathematics (STEM) disciplines, both in Australia and internationally. One debate among CT theorists centres on whether CT comprises a set of generalizable skills or is content- and context-dependent. While previous studies have considered CT skills development and its assessment in pharmacy courses, there appears to have been limited scholarly research within the pharmaceutical sciences discipline. In seeking to address this, it is vital to understand how companies conceptualize CT and its use by Bachelor of Pharmaceutical Sciences graduates. This research identifies five major categories used to conceptualize CT in the companies interviewed: being systematic, having strong business sense, considering multiple solutions, considering implications and identifying problems and potential solutions. The study finds that, while these skills are dependent on the business context, they may be generalizable across a range of industries.